The prognostic value of N6-methyladenosine RBM15 regulators in lung adenocarcinoma - Ma, Mingsheng; Wang, Wei; Wang, Biying; Yang, Yichen; Huang, Yunchao; Zhao, Guangqiang; Ye, Lianhua (Cellular and Molecular Biology, 2022)
N6-methyladenosine (m6A) is the most common internal modification in mammalian mRNAs while RNA-binding motif protein 15 (RBM15) is an important methyltransferase in m6A modification. Increasing evidences have shown that RBM15 has a close correlation with lung cancer. However, specific functions of RBM15 in lung adenocarcinoma (LUAD) are limited. RBM15 expression was analyzed in human LUAD tissues and matched healthy lung tissue. RBM15 was knocked down via siRNA in A549 and H1734 cells. The relationships between RBM15 with cellular functions characteristics and mRNA m6A levels were explored. We performed functional characterization in A549 and H1734 cells lines to elucidate the molecular role of RBM15. Results found that RBM15 was up-regulated in the LUAD tissue and cells, which was linked to poor survival of LUAD patients. RBM15 can be knocked down via siRNA in A549, which leads to the exploration of the associations between RBM15 with cell characteristics. In vivo, RBM15 knockdown could decrease the methylation level, reduce proliferation, accelerate apoptosis and inhibit tumor growth. Our research shows that RBM15 facilitates LUAC cell progression by m6A demethylation. However, it is necessary to conduct further researches on potential downstream molecular mechanisms and m6A modification of RBM15 activity in LUAC.